A study of formation damage caused by oil-based mud in dynamic condition - Ismail, Issham; Thanapala Singam, Murugesu (Penerbit UTM Press, 2005)

(untitled)
Well Productivity Can Be Significantly Affected By Damage Near To Wellbore Area Caused By Drilling. Thus, This Technical Paper Discusses The Formation Damage Caused By Oil-Based Mud On The Berea Sandstone Cores In Simulated Vertical And Horizontal Wells. This Study Was Carried Out In A Dynamic Condition At Various Differentials Pressure. Oil-Based Mud Was Prepared In The Laboratory And Standard Equipments Were Used To Determine The Mud Rheological Properties. Berea Sandstone Cores Were Saturated With Sarapar For 24 Hours Prior To The Tests. The Result Of This Study Was Based On The Measurement Of Filtrate Loss And Core Permeability Measurement Before And After Exposure To Oil-Based Mud In Vertical And Horizontal Conditions At Various Differentials Pressure. The Experimental Results Revealed That The Permeability Impairment Increased As Differential Pressure Increases. However, At Differential Pressure Of 250 Psi (1723.7 Kpa), The Damage Occurred Was Less Severe Compared To 200 Psi (1379.0 Kpa), In Both Vertical And Horizontal Conditions. SEM Image Showed The Presence Of Microfractures In The Core When Exposed To Mud At High Pressure And Temperature, Under Dynamic Condition. Experimental Results Also Showed That The Horizontal Condition Experienced More Severe Damage And Lower Filtrate Loss As Compared To Vertical Condition.